The ways of subjectivity: embodiment of the mental - Faria, Daniel Luporini de [UNESP] (Univ Fed Rondonia, 2016)
Since subjectivity is characterized as a philosophical construction, will trace in the following article, the main views that were thought the subject concepts or self , from Aristotle, through cognitivism, probably dating to the subject metaphysical Cartesian matrix, to compatibilist / realistic version of the early Wittgenstein, for finally bringing to the fore some knowledge of today's dynamic cognitive sciences, for which the role of the body and the direct perception and lived life of a subject no more metaphysical, it would be of vital importance to a new conception of the subject and subjectivity, which was rooted in the world, built and located at the physical and socio-cultural environment.
Keywords: Subject; Metaphysics; Cognitivism; Lived life